Analisis Faktor-Faktor yang Mempengaruhi Peran Perempuan Tani Dalam Usahatani Jagung Pada Sistem Pertanian Lahan Kering di Kecamatan Pujut Kabupaten Lombok Tengah - Dm. Ali, Miftahul Khairat; Hayati, Hayati; Muktasam, Muktasam (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
The purpose of this study is to identify the factors influencing the role of women farmers in maize farming within the dryland agricultural system in Pujut District, Central Lombok Regency. Two villages, Mertak and Sukadana, were selected as research locations, as both have extensive dryland areas suitable for maize cultivation. This study employs a descriptive method. To determine the respondents, "proportional random sampling" was used. Ordinal regression analysis was the data analysis technique applied. The findings indicate that the role of women in maize farming in Pujut District is influenced by multiple factors, with access to technology and markets being the most significant. This suggests that the lower women’s access to technology and markets, the smaller their role in maize farming.